2016
DOI: 10.4038/jas.v11i3.8171
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Novel Carrot-based Synbiotic Beverage using Lactobacillus casei 431®

Abstract: Lactobaccilus casei 431® is a probiotic microorganism, intentionally introduced into fruits and vegetable juices due to its great activity and survivability. Carrot is comprised with many functional food components such as vitamins (A, C, D, and K) minerals (calcium, potassium, phosphorus, sodium, and iron) and prebiotic compounds (Fructo-oligosaccharide (FOS)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
(12 reference statements)
0
2
0
Order By: Relevance
“…Various foods and beverages have been explored as second-generation vehicles for probiotic delivery [20][21][22]. One such class of vehicles are fruits and vegetable matrices [23,24]. However, selection of an appropriate food system as a delivery matrix remains a crucial factor, since the finished products need to have adequate probiotic viability, acceptable sensory attributes and potent bio-efficacies [25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Various foods and beverages have been explored as second-generation vehicles for probiotic delivery [20][21][22]. One such class of vehicles are fruits and vegetable matrices [23,24]. However, selection of an appropriate food system as a delivery matrix remains a crucial factor, since the finished products need to have adequate probiotic viability, acceptable sensory attributes and potent bio-efficacies [25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…But recently, consumer demand has converted to non-diary based probiotic products such as fruits and vegetables and cereal based products because of cholesterol level, lactose intolerance which is related to diary product consumption and the increased popularity of vegetarianism. The recent investigations carried out by Gamage, Mihirani, Perera and Weerahewa (2016) and Alwis, Perera, and Weerahewa (2016) indicated that incorporation of Lactobacillus casei 431 in to carrot juice and beet root juice have proven to be use as an effective synbiotic beverage.…”
Section: Introductionmentioning
confidence: 99%